GREEK REACTIONS ON ILINDEN UPRISING (Annual of the Faculty of Philosophy in Skopje, 2012)
The start of the Hindern Uprising in Ottoman Macedonia did not surprised the Greek political circles in Athens. The Greek politicians had a lot of informations about the situation in this restless Ottoman province. However, the uprising in Ottoman Macedonia did not correspond to the Greek interests in the region, having in mind, that Greeks had considered Macedonia as a part of their historic heritage. So, the reactions of the Greek politicians and different nationalist organizations were predictable.
Keywords: GREECE; RALLIS; ILINDEN UPRISING; MACEDONIA; CENTRAL MACEDONIANSYLLOGOS